Maharah Kalam Learning in Higher Education Using a Collaborative Learning Based on Constructivism Theory - Muhammad Rizal Falaqi; Nur Qomari; Apri Wardana Ritonga (Journal of Advanced Research in Social Sciences and Humanities, 2023)
Aim: Speaking skills are one of the main skills that must be mastered by students and are one of the ultimate goals of learning a foreign language. On that basis, various strategies based on learning theories have been developed to facilitate the process of language acquisition and learning Arabic. One of these theories is the constructivism theory. Constructivism theory understands learning as a process of forming (constructing) knowledge by the learner themselves. This study aims to explore the implementation of constructivism theory in teaching speaking skills in the Arabic Language Education Department, State Islamic University of Salatiga, Indonesia.Methodology: This study was a qualitative study with a case study. Data were collected through observation, in depth interviews, and documentation. The analysis technique used was data triangulation. In the data analysis process, the researcher used the following steps: data collection, data reduction, data presentation, and drawing conclusions.Findings: Study brings key policy insights for learning and teaching higher authorities and governing bodies. The implementation of collaborative learning based on constructivism theory in teaching speaking skills is carried out with several strategies, namely: role play and drama, three-step interview, debate, and language games.